2021
DOI: 10.4049/jimmunol.2000133
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Nonseasonal Longitudinal Variation of Immune Function

Abstract: Different components of the immune response show large variability between individuals, but they also vary within the same individual because of host and environmental factors. In this study, we report an extensive analysis of the immune characteristics of 56 individuals over four timepoints in 1 single year as part of the Human Functional Genomics Project. We characterized 102 cell subsets using flow cytometry; quantified production of eight cytokines and two chemokines in response to 20 metabolic, bacterial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
4
15
1
Order By: Relevance
“…Ter Horst et al. (2021) also suggest a seasonality in some responses ( 140 ), and anecdotally this has been observed in BD patients with worsening symptoms during autumn. Age related changes have also been cited by these studies and IL-6 associated quantitative trait loci were identified.…”
Section: Discussionmentioning
confidence: 98%
“…Ter Horst et al. (2021) also suggest a seasonality in some responses ( 140 ), and anecdotally this has been observed in BD patients with worsening symptoms during autumn. Age related changes have also been cited by these studies and IL-6 associated quantitative trait loci were identified.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, including the patients' age did not improve the RF model performance. Age has been evaluated extensively in the past also using the same flow cytometry panels used in the current study [16,17]. Although aging influences the immune cell composition (e.g., young vs old), within the age-interval (mean age 44-56) of our study cohort, as expected and as analyzed, the outcome of the RF model was hardly influenced.…”
Section: Discussionmentioning
confidence: 61%
“…All antibodies were titrated and tested before use. Percentages of immune cell subsets were manually analyzed using Kaluza software version 2.1 (Beckman-Coulter, Brea, CA, USA) as described previously [16,17,19].…”
Section: Methodsmentioning
confidence: 99%
“…Seasonality is an important environmental factor that influences immune responses ( 46 , 47 ). Samples from 100 melanoma patients (Stage II, III and IV) which were stained using the MoT test were collected from December 2020 until June 2021.…”
Section: Resultsmentioning
confidence: 99%